BUKU DAN OBSESI: SEBUAH ANALISIS NEW HISTORICISM PADA 'THE MAN WHO LOVED BOOKS TOO MUCH' - Mohammad Ricky Ramadhan Rasyid; Shafwan Nugraha (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2024)
Obsession with books often reflects broader social and cultural values. This research aims to understand the phenomenon of book obsession through a New Historicism approach, focusing on the cases of John Charles Gilkey and Ken Sanders. The method used is a qualitative case study with textual and contextual analysis of the book "The Man Who Loved Books Too Much" by Allison Hoover Bartlett. The findings show that Gilkey's obsession with books was driven not only by a love of literature, but also by a desire for social recognition and status. Gilkey's behavior, often breaking the law to acquire rare books, reflects how individuals can sacrifice social norms to achieve personal goals influenced by historical and cultural contexts. In contrast, Sanders' dedication to protecting and preserving rare books shows the positive side of book obsession, where it contributes to the preservation of knowledge and cultural heritage. This research provides insight into the dynamics of book obsession and how social and cultural values can influence individual behavior. Keywords: Culture, Books, New Historicism, Obsession